2020
DOI: 10.1186/s13071-020-04138-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antigenicity and protective efficacy of Leishmania promastigote membrane antigens in search of potential diagnostic and vaccine candidates against visceral leishmaniasis

Abstract: Background Visceral leishmaniasis (VL), is a parasitic disease that causes serious medical consequences if treatment is delayed. Despite a decline in the number of VL cases in the Indian subcontinent, the commencement of the disease in newer areas continues to be a major concern. Although serological diagnosis mainly by immunochromatographic tests has been found to be effective, a test of cure in different phases of treatment is still desired. Even though a good prophylactic response has been o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Immuno-proteomic techniques are now extensively used to define immunogenic candidates in both promastigote and amastigote antigens [ 51 53 ]. Based on several previous studies highlighting the presence of highly immunogenic antigens in the promastigote form that initiates infection [ 54 56 ], we designed our prophylactic vaccine with total antigens from promastigote and identified the optimal mode of administration. Interestingly, no liver and spleen biopsies from IN LdAg vaccinated mice yielded viable parasites in vitro , suggesting significant protection against promastigote infection.…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-proteomic techniques are now extensively used to define immunogenic candidates in both promastigote and amastigote antigens [ 51 53 ]. Based on several previous studies highlighting the presence of highly immunogenic antigens in the promastigote form that initiates infection [ 54 56 ], we designed our prophylactic vaccine with total antigens from promastigote and identified the optimal mode of administration. Interestingly, no liver and spleen biopsies from IN LdAg vaccinated mice yielded viable parasites in vitro , suggesting significant protection against promastigote infection.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the studies, L. donovani proteins of different molecular weights such as 31, 34, 36, 45, 51, 63, 72, 91, and 97 kDa were purified and evaluated in a serological ELISA. It was observed that 34 and 51 kDa proteins showed 100% sensitivity and no cross-reactivity with other diseases [ 287 ]. Advancement in molecular biology led to the discovery of more defined recombinant proteins that were easier in purification with no batch-to-batch variation, unlike crude proteins.…”
Section: Approaches In Leishmania Diagnosis and Th...mentioning
confidence: 99%
“…Leishmanial membrane antigen (LAg) was isolated from the promastigotes of L. donovani strain AG83 (ATCC ® PRA-413 ™ ) according to the protocol discussed earlier (Ejazi et al, 2020). In an indirect ELISA, Brazilian sera from UFPI were tested for antibodies against LAg.…”
Section: Elisamentioning
confidence: 99%